Speaking Anxiety and Linguistic Hurdles: A Mixed-Methods Study of EFL Student-Teachers in Indonesia - Nur Amelia Putri (CV. Lentera Literasi Indonesia, 2026)
Speaking skills hold a central position in English language acquisition, particularly for students enrolled in English Education programs who are being prepared to serve as prospective teachers. Despite its importance, a considerable number of learners of English as a Foreign Language (EFL) still encounter persistent obstacles in developing effective speaking abilities. This research seeks to identify and examine the speaking-related difficulties experienced by fourth-semester students of class 4.A1 in the English Education Study Program at Universitas Muhammadiyah Tangerang. Employing a mixed-methods research design, data were obtained through online interviews administered via Google Forms and supported by classroom observation. The results indicate that students frequently struggle with issues such as hesitation during speech, insufficient vocabulary mastery, grammatical inaccuracies, pronunciation difficulties, and a lack of self-confidence. These challenges stem not only from linguistic shortcomings but also from psychological factors, including anxiety and fear of making errors while speaking. The findings underline the urgency of implementing comprehensive instructional strategies that simultaneously foster linguistic development and address affective aspects by creating a supportive learning atmosphere and increasing opportunities for oral practice. The originality of this study is reflected in its mixed-methods approach, which focuses on the interaction between linguistic competence and psychological constraints among Indonesian EFL pre-service teachers. Overall, this study offers meaningful contributions to understanding EFL speaking challenges and emphasizes the necessity of integrating language instruction with emotional support, with significant implications for curriculum design and teacher education in the Indonesian context.